2018
DOI: 10.19082/6240
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between behavioral indices of pain during labor pain with pain intensity and duration of delivery

Abstract: BackgroundCertain behaviors can be adopted by women to cope with labor pain according to their individual characteristics, which are currently called behavioral indicators during labor pain, and include facial expressions, verbal expressions, tone of voice, body movements, degree of relaxation, and respiratory system functioning during delivery. Moreover, severity of pain and duration of labor can vary due to several factors including individual characteristics.ObjectiveThe purpose of the present study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Mainau and Manteca [ 16 ] established that parturition is a physiological stage in which the perception of acute pain results from uterine contractions, the expulsion of the fetus, and inflammation of the uterine tract. Uterine contractions are necessary, especially during the expulsion phase, when they increase in strength and duration, increasing pain intensity ( Figure 1 ) [ 17 , 18 ].…”
Section: Controversy On the Participation Of Pain During Parturitionmentioning
confidence: 99%
“…Mainau and Manteca [ 16 ] established that parturition is a physiological stage in which the perception of acute pain results from uterine contractions, the expulsion of the fetus, and inflammation of the uterine tract. Uterine contractions are necessary, especially during the expulsion phase, when they increase in strength and duration, increasing pain intensity ( Figure 1 ) [ 17 , 18 ].…”
Section: Controversy On the Participation Of Pain During Parturitionmentioning
confidence: 99%
“…Specifically, fear of labor pain and catastrophizing may lead to considerable worries about the subsequent delivery and requests for a cesarean section (Junge et al, 2021). Additionally, a relationship between the duration of stages of labor and the severity of labor pain has been found (Asl et al, 2018). Moreover, the World Health Organization highlighted the association between high cesarean section rates and adverse neonatal outcomes (Drzymalski et al, 2021; Villar et al, 2006), and a secondary analysis (McKinney et al, 2019) of the Consortium on Safe Labor Project involving 66,940 women found that maternal and neonatal composite morbidity is greater for longer durations of active phase and second stage labor.…”
Section: Introductionmentioning
confidence: 99%